IMPROVING LANGUAGE COMPETENCE OF FUTURE BIOLOGY SPECIALISTS ACCORDING TO CLIL METHOD - Khidoyatova, Shakhlo (Educational Research in Universal Sciences, 2023)
This article introduction lays the groundwork for a research study focused on enhancing language competence among future biology specialists through the Content and Language Integrated Learning (CLIL) method. The introduction outlines the background, emphasizing the specialized language of biology, discusses the significance of the study, and delineates key research objectives. It highlights the global demand for interdisciplinary skills and the need for effective scientific communication within the biology community. The study aims to contribute insights into the application of CLIL in biology education, assess its impact on language competence, explore student perceptions, and examine potential long-term effects on professional careers.